Factors predictive of leg‐ulcer healing in sickle cell disease: a multicentre, prospective cohort study. (1st July 2017) - Senet, P.; Blas‐Chatelain, C.; Levy, P.; Manea, E.M.; Peschanski, M.; Mirault, T.; Stankovic‐Stojanovic, K.; Debure, C.; Debbache, K.; Girot, R.; Bureau, J.‐M.; Bachmeyer, C.; et al.
Summary: Background: Leg ulcers (LUs) are a chronic and severe complication of sickle cell disease (SCD). A prospective study in patients with SCD to identify factors associated with complete healing and recurrence of LUs is lacking. Objectives: To determine clinical and biological factors associated with SCD‐LU complete healing and recurrence. Methods: This prospective, observational cohort study was conducted at two adult SCD referral‐centre sites (2009–2015) and included 98 consecutive patients with at least one LU lasting ≥ 2 weeks. The primary end points compared patients with healed vs. nonhealed LUs at week 24, and patients with vs. without recurrence during follow‐up. Results: The median (interquartile range) LU area, duration and follow‐up were, respectively, 6·2 cm 2 (3–12·8), 9 weeks (4–26) and 65·8 weeks (23·8–122·1). At week 24, LUs were healed in 47% of patients, while 49% of LUs recurred. Univariate analyses identified inclusion LU area < 8 cm 2 (82% vs. 35%; P < 0·001), inclusion LU duration < 9 weeks (65% vs. 35%; P = 0·0013) and high median fetal haemoglobin level ( P = 0·008) as being significantly associated with complete healing at week 24, and low lactate dehydrogenase level ( P = 0·038) as being associated with recurrence. Multivariate analyses retained LU area < 8 cm 2 (odds ratio 6·73, 95% confidence interval 2·35–19. 31; P < 0·001) and < 9 weeks' duration (OR 3·19, 95% confidence interval 1·16–8·76; P = 0·024) as being independently associated with healing at week 24. Factors independently associated with recurrence could not be identified. Conclusions: SCD‐LU complete healing is independently associated with the clinical characteristics of LUs rather than the clinical or biological characteristics of SCD.